IMPLEMENTATION OF SERIAL AND PARALLEL BUBBLE SORT ON FPGA - Dwi Marhaendro Jati Purnomo; Ahmad Arinaldi; Dwi Teguh Priyantini; Ari Wibisono; Andreas Febrian (Faculty of Computer Science - Universitas Indonesia, 2016)
Sorting is common process in computational world. Its utilization are on many fields from research to industry. There are many sorting algorithm in nowadays. One of the simplest yet powerful is bubble sort. In this study, bubble sort is implemented on FPGA. The implementation was taken on serial and parallel approach. Serial and parallel bubble sort then compared by means of its memory, execution time, and utility which comprises slices and LUTs. The experiments show that serial bubble sort required smaller memory as well as utility compared to parallel bubble sort. Meanwhile, parallel bubble sort performed faster than serial bubble sort